The Philosophy of Perennialism and Divine Aspects in the Theory of Educational Service Socialization Implementation at SDN 20 Prabumulih - Mulyani, Sri; Berlian, Zainal; Zainuri, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to describe the implementation of educational service socialization at SDN 20 Prabumulih, with a focus on the methods and strategies used to raise public awareness of the importance of education. The socialization aims to introduce the educational services provided by the school to parents and the surrounding community, as well as to encourage their active participation in supporting the success of their children's education. The research method used is a case study, with a qualitative approach to explore the socialization process, the factors influencing its success, and the challenges faced during its implementation. Data was collected through in-depth interviews with the principal, teachers, parents, and direct observation of the socialization activities conducted. The results of the study indicate that the socialization has been successful but still faces several obstacles, such as low parental participation due to time constraints and lack of knowledge. Additionally, although there has been an improvement in the community's understanding of the available educational services, further efforts are still needed to reach all segments of the community more effectively. This study suggests that socialization activities should be more structured and involve various stakeholders, including community leaders, to increase the positive impact on the quality of education at SDN 20 Prabumulih.